Preparation method of a sandwich structure COFs / MXene composite nanofiltration membrane
Patent Information
- Application Number
- CN202410557374.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-07
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2044-05-07
AI Technical Summary
然而,因为沿径向穿过多孔基板的驱动力(压差)不同,难以制备出无缺陷均匀的膜
[0013](1)本发明通过逐层电泳沉积(LBL EPD)法在基膜表面沉积COFs/MXene复合层,制备具有夹层结构的COFs/MXene复合纳滤膜。其中两侧的超薄MXene层主要起成膜作用,中间COFs层主要起筛分作用。此外,正电性的COFs和负电性的MXene能够通过静电力的作用相互结合,进一步提高复合膜的稳定性。
Smart Images

Figure CN118416709B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of two-dimensional nanocomposite nanofiltration membrane preparation, specifically a method for preparing a sandwich structure COFs / MXene composite nanofiltration membrane. Background Technology
[0002] To date, dyes have been widely used in various industries, such as textiles, packaging, papermaking, and food. Studies have shown that high concentrations of inorganic salts increase the difficulty of dye removal from dye wastewater, and the presence of dyes also makes the recovery of inorganic salts more challenging. Therefore, dye / salt separation is an effective method for treating dye wastewater and an important pathway to achieving sustainable resource utilization. Pressure-driven membrane separation technology has been widely applied in the field of dye wastewater treatment. In particular, nanofiltration membranes, with molecular cutoff values between 200 and 1000 Da, can rapidly separate salts from dye molecules. Although nanofiltration membranes offer ideal separation precision, their operating efficiency is significantly limited due to their relatively low permeability. In past research, various nanoscale materials have been used to improve the permeability of nanofiltration membranes, such as graphene oxide, carbon quantum dots, micene, metal-organic frameworks, and covalent organic frameworks (COFs).
[0003] As an emerging porous framework material, COFs are periodic assemblies of organic units linked by strong covalent bonds. COFs possess many superior properties, including ordered and customizable pores, well-defined pore sizes (1.0–4.8 nm), high and permanent porosity, excellent thermal and chemical stability, and easily customizable functions, making them potentially valuable for applications in catalysis, sensing, gas adsorption, energy storage, and separation. Due to their ordered pores and uniform mass transfer pathways, COFs have become ideal candidate materials for constructing next-generation membranes, especially in molecular separation. Therefore, introducing COF particles into polymers to prepare hybrid matrix membranes is a research direction. However, the non-uniform dispersion of COF particles in polymers hinders the untapped potential of their inherent porosity. In recent years, researchers have successfully fabricated COF membranes using bottom-up strategies, such as interfacial polymerization and solvothermal methods.
[0004] Interfacial polymerization produces COF films with excellent solvent permeability and retention properties, but the resulting films suffer from poor crystallinity and mechanical strength, leading to low preparation efficiency. The solvothermal method involves exposing the substrate to a reactive precursor solution, followed by COF growth on the substrate to form a COF film. However, during growth, COF powder and COF film inevitably form simultaneously, making film thickness difficult to control. Furthermore, researchers have attempted a top-down approach (vacuum-assisted self-assembly) to prepare COF films, where film thickness can be adjusted simply by controlling the concentration and volume of the COF dispersion solution. Therefore, vacuum-assisted self-assembly is currently one of the simplest and most controllable methods for preparing COF films. However, due to varying driving forces (pressure differences) along the radial direction through the porous substrate, it is difficult to prepare defect-free and uniform films. Additionally, the preparation process is typically time-consuming. Therefore, a rapid preparation technology for COF films with uniform and constant driving forces and controllable fabrication is still lacking. Summary of the Invention
[0005] To address the shortcomings of existing technologies, the technical problem this invention aims to solve is to provide a method for preparing a sandwich-structured COFs / MXene composite nanofiltration membrane.
[0006] The technical solution of this invention to solve the aforementioned technical problem is to provide a method for preparing a sandwich-structured COFs / MXene composite nanofiltration membrane, characterized in that the method includes the following steps:
[0007] (1) Preparation of negatively charged MXene nanosheet suspension and positively charged COFs nanosphere suspension;
[0008] (2) Preparation of sandwich-structured COFs / MXene composite nanofiltration membrane;
[0009] (2.1) The microfiltration membrane is placed in an MXene nanosheet suspension, and two electrophoretic electrodes are placed on both sides of the microfiltration membrane. Then, a voltage is applied to deposit MXene on the outer surface of one side of the microfiltration membrane. Then, the membrane is removed, dried to remove the solvent from the membrane surface, and a microfiltration membrane with an MXene layer is obtained.
[0010] (2.2) The microfiltration membrane with the MXene layer obtained in step (2.1) is placed in a COF nanosphere suspension, and two electrophoretic electrodes are placed on both sides of the microfiltration membrane with the MXene layer; then a voltage opposite to that in step (2.1) is applied to deposit COFs on the outer surface of the microfiltration membrane with the MXene layer; then it is taken out, dried to remove the solvent from the membrane surface, and a microfiltration membrane with the MXene layer and COF layer in sequence from the inside to the outside is obtained;
[0011] (2.3) The microfiltration membrane with MXene and COFs layers obtained in step (2.2) is placed in an MXene nanosheet suspension, and two electrophoretic electrodes are set on both sides of the microfiltration membrane with MXene and COFs layers. Then, a voltage in the same direction as in step (2.1) is applied to deposit MXene on the outer surface of the microfiltration membrane with COFs layers on the side with COFs layers. Then, it is taken out, dried to remove the solvent from the membrane surface, and a sandwich structure COFs / MXene composite nanofiltration membrane with COFs in the middle layer and MXene on both sides is obtained.
[0012] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0013] (1) This invention prepares a COFs / MXene composite nanofiltration membrane with a sandwich structure by depositing a COFs / MXene composite layer on the surface of a base membrane using the layer-by-layer electrophoretic deposition (LBL EPD) method. The ultrathin MXene layers on both sides mainly serve the function of film formation, while the middle COFs layer mainly serves the function of sieving. In addition, the positively charged COFs and negatively charged MXene can bond with each other through electrostatic forces, further improving the stability of the composite membrane.
[0014] (2) The highly ordered pore structure of the COFs nanospheres, the ultrathin MXene layer, and the abundant slits between the COFs nanospheres in the sandwich structure COFs / MXene composite nanofiltration membrane prepared by this invention ensures short and continuous mass transfer channels, resulting in high permeability and high retention rate. Furthermore, this excellent performance remains stable within a pH range of 3–11 and during long-term use.
[0015] (3) The sandwich structure of the COFs / MXene composite nanofiltration membrane is uniform, defect-free, and of uniform thickness. The thickness of the MXene layer and the COFs layer can be adjusted by regulating the deposition voltage, deposition time, and deposition solution concentration during the LBLEPD process, thereby achieving precise control over the thickness of each layer of the COFs / MXene composite nanofiltration membrane.
[0016] (4) The sandwich-structured COFs / MXene composite nanofiltration membrane possesses excellent stiffness and mechanical strength, enabling stable use under high transmembrane pressure. In summary, the COFs / MXene composite nanofiltration membrane highlights the advantages of COFs in the field of nanofiltration, exhibiting excellent nanofiltration performance and dye / salt separation performance. This invention provides a new strategy for the design of COFs membranes to achieve efficient and precise molecular separation.
[0017] (5) The present invention directly prepares a uniform and stable COFs nanosphere suspension, which can be directly used for subsequent EPD experiments, avoiding the step of redispersing COFs microcrystalline powder prepared by conventional methods in a solvent, and the process is simpler and more convenient.
[0018] (6) This invention improves upon conventional electrophoresis apparatus, resulting in a deposited film located far from the electrode. This effectively avoids the formation of defective deposited films on the electrode during conventional EPD processes. Electrolysis causes bubbles and acid / alkali microenvironments to form near the electrode, thereby damaging the film's structure and integrity.
[0019] (7) The preparation process of this invention is simple, efficient and controllable. The prepared COFs / MXene composite nanofiltration membrane is easy to adjust and has potential application prospects in the field of nanofiltration. It has good potential for industrial scale-up application. Attached Figure Description
[0020] Figure 1 This is a diagram illustrating the preparation mechanism of step (2) in this embodiment of the invention;
[0021] Figure 2 This is a schematic diagram of the mold used in an embodiment of the present invention;
[0022] Figure 3 Zeta potential diagram of MXene nanosheets and COFs nanospheres prepared in step (1) of Example 1 of the present invention;
[0023] Figure 4 The XRD pattern of the MXene nanosheets prepared in step (1) of Example 1 of this invention;
[0024] Figure 5 TEM image of MXene nanosheets prepared in step (1) of Example 1 of this invention and Tyndall effect image of the suspension;
[0025] Figure 6 The XRD pattern of the COF nanospheres prepared in step (1) of Example 1 of this invention and the Tyndall effect diagram of the suspension;
[0026] Figure 7 TEM image of COF nanospheres prepared in step (1) of Example 1 of this invention;
[0027] Figure 8 The FITR image of the COF nanospheres prepared in step (1) of Example 1 of this invention;
[0028] Figure 9 The surface SEM image of the sandwich structure COFs / MXene composite nanofiltration membrane prepared in step (2.3) of Example 1 of the present invention;
[0029] Figure 10 The surface SEM image of the microfiltration membrane with MXene layer and COFs layer prepared in step (2.2) of Example 1 of the present invention;
[0030] Figure 11 The image shows a cross-sectional SEM image of the sandwich-structured COFs / MXene composite nanofiltration membrane prepared in step (2.3) of Example 1 of this invention.
[0031] Figure 12 The surface SEM image of the MXene composite film with two MXene layers prepared in step (2.2) of Comparative Example 1 of the present invention;
[0032] Figure 13 The surface SEM image of the MXene composite film with an MXene layer prepared in step (2.1) of Comparative Example 1 of the present invention;
[0033] Figure 14 A cross-sectional SEM image of the MXene composite film with two MXene layers prepared in step (2.2) of Comparative Example 1 of the present invention;
[0034] Figure 15 The image shows a cross-sectional SEM image of the sandwich-structured COFs / MXene composite nanofiltration membrane prepared in step (2.3) of Example 2 of this invention.
[0035] Figure 16 The image shows a cross-sectional SEM image of the sandwich-structured COFs / MXene composite nanofiltration membrane prepared in step (2.3) of Example 3 of this invention.
[0036] Figure 17 The image shows a cross-sectional SEM image of the sandwich-structured COFs / MXene composite nanofiltration membrane prepared in step (2.3) of Example 4 of this invention.
[0037] Figure 18 The image shows a cross-sectional SEM image of the sandwich-structured COFs / MXene composite nanofiltration membrane prepared in step (2.3) of Example 5 of this invention.
[0038] Figure 19 The surface SEM image of the microfiltration membrane with MXene layer and COFs layer prepared in step (2.2) of Comparative Example 4 of the present invention;
[0039] Figure 20 The image shows a surface SEM image of the sandwich-structured COFs / MXene composite nanofiltration membrane prepared in step (2.3) of Comparative Example 4 of this invention. Detailed Implementation
[0040] Specific embodiments of the present invention are given below. These specific embodiments are only used to further illustrate the present invention in detail and do not limit the scope of protection of the claims of the present invention.
[0041] This invention provides a method for preparing a sandwich-structured COFs / MXene composite nanofiltration membrane (hereinafter referred to as the method), characterized in that the method includes the following steps:
[0042] (1) Preparation of negatively charged MXene nanosheet suspension and positively charged COFs nanosphere suspension;
[0043] Preferably, in step (1), the preparation of the negatively charged MXene nanosheet suspension is specifically: the negatively charged MXene nanosheet suspension is prepared by selective in-situ etching of MAX phase.
[0044] Preferably, in step (1), the specific steps of the selective in-situ etching method of the MAX phase are as follows: titanium carbide, lithium fluoride and hydrochloric acid are mixed evenly, and then heated to etch the intermediate layer of the MAX phase. After the reaction is completed, the mixture is washed, centrifuged, sonicated and centrifuged in sequence to obtain a negatively charged MXene nanosheet suspension.
[0045] The mass ratio of titanium carbide, lithium fluoride, and hydrochloric acid is 1–5 g: 2–10 g: 20–80 ml; the concentration of hydrochloric acid is 3–9 mol / L.
[0046] The heating reaction process is as follows: under stirring conditions, the reaction temperature is 35-60℃, the reaction time is 24-48h, and the stirring speed is 200-500rpm (magnetic stirring is preferred);
[0047] The specific process of washing, centrifugation, sonication and centrifugation is as follows: the product is washed with deionized water and then centrifuged until the solution is neutral; then the lower precipitate is dispersed in deionized water and sonicated until MXene is peeled off into monolayer nanosheets; finally, the supernatant is collected by centrifugation.
[0048] Preferably, in step (1), the preparation of the positively charged COFs nanosphere suspension is specifically as follows: the amino monomer and the aldehyde monomer are dissolved in a composite solvent to form a homogeneous mixed solution; then a catalyst is added, and then the solution is allowed to stand to allow the COFs nanospheres to grow fully, thereby obtaining a uniformly dispersed COFs nanosphere suspension.
[0049] Preferably, in step (1), the molar ratio of the amino group in the amino monomer to the aldehyde group in the aldehyde monomer is 1:1; the concentrations of both the amino monomer and the aldehyde monomer are 0.1–5 mmol / L (preferably 0.1–3 mmol / L); the concentration of the catalyst is 0.01–2 mmol / L (preferably 0.01–1 mmol / L); the standing temperature is room temperature; and the standing time is 24–72 h.
[0050] Preferably, in step (1), the amino monomer is 1,3,5-tris(4-aminobenzene), p-phenylenediamine, or benzidine (preferably 1,3,5-tris(4-aminobenzene)).
[0051] The aldehyde monomer is terephthalaldehyde, 2,5-dihydroxyterephthalaldehyde, 2,5-dimethoxyterephthalaldehyde, 1,3,5-tricarboxyloylphloroglucinol or benzene-1,3,5-tricarboxaldehyde (preferably terephthalaldehyde and 2,5-dihydroxyterephthalaldehyde).
[0052] The composite solvent consists of a main solvent and a co-solvent, with the main solvent accounting for 50-100% of the volume of the composite solvent; the main solvent is water, ethanol, acetonitrile, dichloromethane, dioxane, or mesitylene (preferably dichloromethane and ethanol); the co-solvent is acetonitrile, methyl acetate, ethyl acetate, n-butanol, or ethanol (preferably acetonitrile);
[0053] The catalyst is glacial acetic acid, trifluoroacetic acid, scandium trifluoromethanesulfonate, p-toluenesulfonic acid, or a transition metal nitrate (preferably glacial acetic acid, trifluoroacetic acid, or scandium trifluoromethanesulfonate).
[0054] Preferably, in step (1), a positively charged modifier is added to the mixed solution and then allowed to stand; the positively charged modifier is polyethyleneimine, KH570, KH550 or polyacrylic acid; the concentration of the positively charged modifier is 0.01 to 0.05 mmol / L.
[0055] (2) Preparation of sandwich-structured COFs / MXene composite nanofiltration membranes, such as Figure 1 As shown;
[0056] (2.1) The microfiltration membrane is placed in an MXene nanosheet suspension, and two electrophoretic electrodes are placed on both sides of the microfiltration membrane. Then, a voltage is applied to deposit MXene on the outer surface of one side of the microfiltration membrane. Then, the membrane is removed, dried to remove the solvent from the membrane surface, and the MXene layer (i.e. the first layer) is deposited, thus obtaining a microfiltration membrane with an MXene layer.
[0057] Preferably, in step (2.1), the microfiltration base membrane is a polyamide microporous membrane; the microfiltration base membrane is fully expanded; and the microfiltration base membrane is set vertically.
[0058] Preferably, in step (2.1), the concentration of the MXene nanosheet suspension is 0.01–0.1 mg / mL, and the solvent is methanol or ethanol.
[0059] Preferably, in step (2.1), the two electrophoresis electrodes and the microfiltration membrane are parallel to each other, and the microfiltration membrane is located on the vertical line between the two electrophoresis electrodes; in this embodiment, the distance between the two electrophoresis electrodes and the microfiltration membrane is 1 to 5 cm.
[0060] Preferably, in step (2.1), the voltage is 10 to 60V and the duration is 0.5 to 3 minutes.
[0061] (2.2) The microfiltration membrane with the MXene layer obtained in step (2.1) is placed in a COF nanosphere suspension, and two electrophoretic electrodes are set on both sides of the microfiltration membrane with the MXene layer; then a voltage opposite to that in step (2.1) is applied to deposit COFs on the outer surface of the side of the microfiltration membrane with the MXene layer; then it is taken out, dried to remove the solvent from the membrane surface, and the COF layer (i.e. the second layer) deposition is completed, and a microfiltration membrane with the MXene layer and COF layer in sequence from the inside to the outside is obtained;
[0062] Preferably, in step (2.2), the microfiltration membrane with the MXene layer is fully expanded; the microfiltration membrane with the MXene layer is set vertically.
[0063] Preferably, in step (2.2), the concentration of the COFs nanosphere suspension is 0.01–0.1 mg / mL, and the solvent is methanol or ethanol.
[0064] Preferably, in step (2.2), the two electrophoresis electrodes and the microfiltration membrane with the MXene layer are parallel to each other, and the microfiltration membrane with the MXene layer is located on the vertical line between the two electrophoresis electrodes; in this embodiment, the distance between the two electrophoresis electrodes and the microfiltration membrane with the MXene layer is 1 to 5 cm.
[0065] Preferably, in step (2.2), the voltage is 10 to 60V and the duration is 1 to 20 minutes (preferably 4 to 8 minutes).
[0066] (2.3) The microfiltration membrane with MXene and COFs layers obtained in step (2.2) is placed in an MXene nanosheet suspension, and two electrophoretic electrodes are set on both sides of the microfiltration membrane with MXene and COFs layers. Then, a voltage in the same direction as in step (2.1) is applied to deposit MXene on the outer surface of the microfiltration membrane with COFs layers on the side with COFs layers. Then, the membrane is removed, dried to remove the solvent from the membrane surface, and the deposition of the MXene layer (i.e. the third layer) is completed, resulting in a sandwich structure COFs / MXene composite nanofiltration membrane with COFs in the middle and MXene on both sides.
[0067] Preferably, in step (2.3), the microfiltration membrane with the MXene layer and the COFs layer is fully expanded; the microfiltration membrane with the MXene layer and the COFs layer is set vertically.
[0068] Preferably, in step (2.3), the concentration of the MXene nanosheet suspension is 0.01–0.1 mg / mL, and the solvent is methanol or ethanol.
[0069] Preferably, in step (2.3), the two electrophoresis electrodes and the microfiltration membrane with MXene and COFs layers are parallel to each other, and the microfiltration membrane with MXene and COFs layers is located on the vertical line between the two electrophoresis electrodes; in this embodiment, the distance between the two electrophoresis electrodes and the microfiltration membrane with MXene and COFs layers is 1 to 5 cm.
[0070] Preferably, in step (2.3), the voltage is 10 to 60V and the duration is 0.5 to 3 minutes.
[0071] Preferably, in steps (2.1)-(2.3), the electrophoresis electrode is made of conductive material, such as a graphite plate; the drying is carried out by natural air drying at room temperature or vacuum drying at 20-80°C.
[0072] The sandwich-structured COFs / MXene composite nanofiltration membrane obtained by this invention is applied to the separation of dyes / salts in the field of dye wastewater treatment.
[0073] The test method in this embodiment is as follows: An oil-water emulsion separation experiment was conducted at 1 bar using a terminal filtration method. Permeability was calculated using P = V / (A × Δt × ΔP), and separation efficiency was calculated using R = (1 - Cp / Cf) × 100%. Where P, V, A, Δt, ΔP, Cp, and Cf represent the membrane permeability (L / m³). 2 (·h·bar), filtrate volume (L), effective membrane area (m²) 2 The parameters included running time (h), transmembrane pressure (bar), concentration of dye or salt in the filtrate, and concentration of dye or salt in the feed solution. The concentrations of dye and salt were determined using a UV-Vis spectrophotometer (Nanodrop 2000c, Thermo Fisher Scientific) and a conductivity meter (FE38, Mettler Toledo), respectively.
[0074] Example 1
[0075] (1) Preparation of negatively charged MXene nanosheet suspension and positively charged COFs nanosphere suspension;
[0076] Preparation of negatively charged MXene nanosheet suspension: 2g titanium carbide, 3.2g lithium fluoride and 40mL of 9mol / L hydrochloric acid were mixed and reacted at 40℃ with a stirring rate of 500rpm for 24h. After the reaction, the product was washed with deionized water and centrifuged repeatedly at 3500rpm until the solution was neutral. Then the lower precipitate was dispersed in deionized water and sonicated at 0℃ under a nitrogen atmosphere for 1h. Finally, the supernatant was collected by centrifugation at 3500rpm for 30min to obtain the MXene nanosheet suspension.
[0077] Preparation of positively charged COF nanosphere suspension: 2 mmol / L of 1,3,5-tris(4-aminobenzene)benzene and 3 mmol / L of terephthalaldehyde were added to a composite solvent consisting of 700 mL of ethanol and 300 mL of acetonitrile. After ultrasonic dissolution, 0.05 mmol / L of trifluoroacetic acid was added, and then the mixture was allowed to stand at room temperature for 72 h to obtain a uniformly dispersed COF nanosphere suspension.
[0078] (2) Preparation of sandwich-structured COFs / MXene composite nanofiltration membranes by LBL EPD method;
[0079] (2.1) After preparing the MXene nanosheet suspension into a 0.03 mg / mL ethanol solution, it was added to a container; then the microfiltration membrane was fixed in a mold with a hollowed-out center (the mold material was polyimide, such as...). Figure 2 As shown in the figure, the mold is then vertically fixed in the center of the container, and two graphite plates are used as electrophoresis electrodes and fixed on both sides of the mold in parallel and equidistant (1 cm each); then a voltage of 30V is applied and maintained for 1 minute. After that, the mold is removed and allowed to air dry naturally until there is no solvent on the membrane surface. The MXene layer deposition is completed, and a microfiltration membrane with an MXene layer is obtained.
[0080] (2.2) After preparing the COFs nanosphere suspension into an ethanol solution of 0.06 mg / mL, it was added to a container; then the mold of the microfiltration membrane with the MXene layer was fixed in the center of the container, and two graphite plates were used as electrophoresis electrodes and fixed on both sides of the mold in parallel and at equal distances (1 cm each); then a voltage of 30 V opposite to that in step (2.1) was applied and maintained for 6 min. After that, the mold was removed and allowed to air dry naturally until there was no solvent on the membrane surface. The COFs layer deposition was completed, and a microfiltration membrane with an MXene layer and a COFs layer from the inside to the outside was obtained.
[0081] (2.3) After preparing the MXene nanosheet suspension into an ethanol solution of 0.03 mg / mL, it was added to the container; then the mold of the microfiltration membrane with the MXene layer and the COFs layer was fixed in the center of the container, and then the mold was vertically fixed in the center of the container. Then, two graphite plates were used as electrophoresis electrodes and fixed on both sides of the mold in parallel and equidistant (1 cm each); then a voltage of 30 V in the same direction as in step (2.1) was applied and held for 1 min. After that, the mold was removed and vacuum dried at 40 °C. The MXene layer was deposited and a sandwich structure COFs / MXene composite nanofiltration membrane with COFs in the middle and MXene on both sides was obtained.
[0082] Depend on Figure 3 It can be seen that step (1) of Example 1 successfully prepared negatively charged MXene and positively charged COFs.
[0083] Depend on Figure 4 and Figure 5 It can be seen that the MXene nanosheet suspension was successfully synthesized through step (1) of Example 1.
[0084] Depend on Figures 6-8 It can be seen that the COFs nanosphere suspension was successfully synthesized through step (1) of Example 1.
[0085] Depend on Figures 9-11 As can be seen, a COFs / MXene composite nanofiltration membrane with a sandwich structure was successfully prepared through Example 1, and MXene and COFs can form a uniform deposition layer after each LBL EPD.
[0086] Furthermore, tests showed that the COFs / MXene composite nanofiltration membrane exhibits excellent dye separation performance, with a permeability of 200.2 L / m³. 2 The membrane exhibits a high rejection rate of 98.9% for Congo red (·h·bar). Furthermore, this excellent performance remains stable even within a pH range of 3–11 and during long-term use. Simultaneously, the COFs / MXene composite nanofiltration membrane demonstrates superior dye / salt separation performance, achieving a separation factor of 121.1 for Congo red / NaCl.
[0087] Comparative Example 1
[0088] Comparative Example 1 is exactly the same as Example 1, except that: in step (1), only a negatively charged MXene nanosheet suspension is prepared; in step (2), only steps (2.1) and (2.3) of Example 1 are used, that is, only two ultrathin MXene layers are deposited by LBL EPD, and the intermediate COFs layer in step (2.2) is not deposited. Specifically:
[0089] (1) Preparation of negatively charged MXene nanosheet suspension and positively charged COFs nanosphere suspension;
[0090] Preparation of negatively charged MXene nanosheet suspension: 2g titanium carbide, 3.2g lithium fluoride and 40mL of 9mol / L hydrochloric acid were mixed and reacted at 40℃ with a stirring rate of 500rpm for 24h. After the reaction, the product was washed with deionized water and centrifuged repeatedly at 3500rpm until the solution was neutral. Then the lower precipitate was dispersed in deionized water and sonicated at 0℃ under a nitrogen atmosphere for 1h. Finally, the supernatant was collected by centrifugation at 3500rpm for 30min to obtain the MXene nanosheet suspension.
[0091] (2) Preparation of MXene composite membranes by LBL EPD method;
[0092] (2.1) After preparing the MXene nanosheet suspension into an ethanol solution of 0.03 mg / mL, it was added to a container; then the microfiltration membrane was fixed on the hollowed-out mold, and the mold was then vertically fixed in the center of the container. Two graphite plates were then used as electrophoresis electrodes and fixed parallel to each other (1 cm apart) on both sides of the mold; then a voltage of 30 V was applied and held for 1 min. After that, the mold was removed and allowed to air dry naturally until there was no solvent on the membrane surface. The MXene layer deposition was completed, and an MXene composite membrane with one MXene layer was obtained.
[0093] (2.2) After preparing the MXene nanosheet suspension into an ethanol solution of 0.03 mg / mL, it was added to the container; then the mold of the microfiltration membrane with the MXene layer was fixed in the center of the container, and then the mold was vertically fixed in the center of the container. Then, two graphite plates were used as electrophoresis electrodes and fixed on both sides of the mold in parallel and equidistant (1 cm each); then a voltage of 30 V in the same direction as in step (2.1) was applied and held for 1 min. After that, the mold was removed and vacuum dried at 40 °C. The MXene layer deposition was completed, and an MXene composite membrane with two MXene layers was obtained.
[0094] Depend on Figures 12-14 As can be seen, a composite film with two MXene layers was successfully prepared by Comparative Example 1, and MXene was uniformly deposited after each LBL EPD.
[0095] Tests showed that MXene without a COF layer had extremely high permeability, but no dye retention capacity. This indicates that the COF layer plays a major sieving role, and the ultrathin MXene layer has limited dye retention capacity.
[0096] Comparative Example 2
[0097] Comparative Example 2 is exactly the same as Example 1, except that the preparation of the COFs nanosphere suspension in step (1) of Example 1 is replaced with COFs powder prepared in the literature "Xu H, Gao J, Jiang D. Nature Chemistry, 2015, 7:905-12". Specifically:
[0098] (1) Preparation of COFs powder dispersion: 0.08 mmol of 1,3,5-tris(4-aminobenzene), 0.12 mmol of terephthalaldehyde, 0.1 mL of catalyst-glacial acetic acid and 1 mL of mixed solvent (0.5 mL n-butanol and 0.5 mL o-dichlorobenzene) were added to a 10 mL Pyrex tube. After degassing by three freeze-pump-thaw cycles, the Pyrex tube was sealed with a flame and heated at 120 °C for three days. The precipitate was collected by centrifugation, washed with THF, and then Soxhlet extracted with THF as solvent for one day. The powder was collected and heated under vacuum at 120 °C for 12 h to obtain COFs powder. The COFs were then dispersed in a composite solvent consisting of 700 mL ethanol and 300 mL acetonitrile and sonicated for 4 h to obtain COFs powder dispersion.
[0099] Testing revealed that a uniformly dispersed COFs powder dispersion could not be obtained in step (1). After standing for 5 minutes, the COFs powder would settle. During the LBL EPD process, the COFs powder could not be uniformly deposited on the base membrane, resulting in a defective COFs / MXene composite nanofiltration membrane with poor nanofiltration performance.
[0100] Comparative Example 3
[0101] Comparative Example 3 is exactly the same as Example 1, except that only steps (2.1) and (2.2) are used in step (2), and step (2.3) is not performed.
[0102] Tests showed that without step (2) and step (2)3 of step (2), a COFs / MXene composite nanofiltration membrane with an outer layer of COFs and an inner layer of MXene was formed. During the test, the COFs nanospheres would fall off, so the nanofiltration test could not be performed.
[0103] Comparative Example 4
[0104] Comparative Example 4 is exactly the same as Example 1, except that the LBL EPD method in step (2) is replaced with a layer-by-layer vacuum-assisted self-assembly method, specifically:
[0105] (2) Layer-by-layer vacuum-assisted self-assembly method for preparing sandwich-structured COFs / MXene composite nanofiltration membranes;
[0106] (2.1) The MXene nanosheet suspension was prepared into an ethanol solution of 0.03 mg / mL. Then, the microfiltration membrane was fixed on the vacuum filtration device. Subsequently, the MXene nanosheet suspension was poured into the filter cup for vacuum-assisted self-assembly. After filtration, it was naturally air-dried until there was no solvent on the membrane surface. The MXene layer was deposited and a microfiltration membrane with an MXene layer was obtained.
[0107] (2.2) The COFs nanosphere suspension was prepared into an ethanol solution of 0.06 mg / mL. Then, the microfiltration membrane with the MXene layer was fixed on the vacuum filtration device. Subsequently, the COFs nanosphere suspension was poured into the filter cup for vacuum-assisted self-assembly. After filtration, it was naturally air-dried until there was no solvent on the membrane surface and the COFs layer was deposited. A microfiltration membrane with the MXene layer and COFs layer from the inside to the outside was obtained.
[0108] (2.3) The MXene nanosheet suspension was prepared into an ethanol solution of 0.03 mg / mL. Then, the microfiltration membrane with MXene layer and COFs layer was fixed on the vacuum filtration device. Subsequently, the MXene nanosheet suspension was poured into the filter cup for vacuum-assisted self-assembly. After the filtration was completed, the base membrane was taken out and vacuum dried at 40℃. The MXene layer was deposited and a sandwich structure COFs / MXene composite nanofiltration membrane with COFs in the middle and MXene on both sides was obtained.
[0109] After testing, such as Figure 19 and Figure 20 As shown, due to uneven stress, the COFs / MXene composite nanofiltration membrane prepared by layer-by-layer vacuum-assisted self-assembly has defects, and the prepared COFs / MXene composite nanofiltration membrane cannot retain dye.
[0110] Example 2
[0111] Example 2 is exactly the same as Example 1, except that the deposition time in step (2.2) of step (2) is 2 min.
[0112] Tests showed that the COFs / MXene composite nanofiltration membrane exhibits excellent dye separation performance, with a permeability of 325.0 L / m³. 2 The membrane exhibits a high rejection rate of 68.4% for H·bar and Congo Red, and a thickness of 211 nm. Furthermore, this excellent performance remains stable even within a pH range of 3–11 and during long-term use. Simultaneously, the COFs / MXene composite nanofiltration membrane also demonstrates excellent dye / salt separation performance.
[0113] Example 3
[0114] Example 3 is exactly the same as Example 1, except that the deposition time in step (2.2) of step (2) is 4 min.
[0115] Tests showed that the COFs / MXene composite nanofiltration membrane exhibits excellent dye separation performance, with a permeability of 262.5 L / m³. 2 The membrane exhibits a high rejection rate of 90.2% for H·bar and Congo Red, and its thickness is 440 nm. Furthermore, this excellent performance remains stable even within a pH range of 3–11 and during long-term use. Simultaneously, the COFs / MXene composite nanofiltration membrane also demonstrates superior dye / salt separation performance.
[0116] Example 4
[0117] Example 4 is exactly the same as Example 1, except that the deposition time in step (2.2) of step (2) is 8 min.
[0118] Tests showed that the COFs / MXene composite nanofiltration membrane exhibits excellent dye separation performance, with a permeability of 135.6 L / m³. 2 The membrane exhibits a high rejection rate of 99.3% for H·bar and Congo Red, and its thickness is 903 nm. Furthermore, this excellent performance remains stable even within a pH range of 3–11 and during long-term use. Simultaneously, the COFs / MXene composite nanofiltration membrane also demonstrates superior dye / salt separation performance.
[0119] Example 5
[0120] Example 5 is exactly the same as Example 1, except that the deposition time in step (2.2) of step (2) is 10 min.
[0121] Tests showed that the COFs / MXene composite nanofiltration membrane exhibits excellent dye separation performance, with a permeability of 116.4 L / m³. 2 The membrane exhibits a high rejection rate of 99.5% for H·bar and Congo Red, and a thickness of 950 nm. Furthermore, this excellent performance remains stable even within a pH range of 3–11 and during long-term use. Simultaneously, the COFs / MXene composite nanofiltration membrane also demonstrates excellent dye / salt separation performance.
[0122] Depend on Figure 11 and Figures 15-18 A comparison (i.e., comparing Example 1 with Examples 2-5) reveals that the COFs / MXene composite nanofiltration membrane with a sandwich structure can be controlled by changing the deposition time.
[0123] Example 6
[0124] (1) Preparation of negatively charged MXene nanosheet suspension and positively charged COFs nanosphere suspension;
[0125] Preparation of negatively charged MXene nanosheet suspension: 5g titanium carbide, 4g lithium fluoride and 80mL 6mol / L hydrochloric acid were mixed and reacted at 50℃ with a stirring rate of 200rpm for 48h. After the reaction, the product was washed with deionized water and centrifuged repeatedly at 3500rpm until the solution was neutral. Then the lower precipitate was dispersed in deionized water and sonicated at 0℃ under a nitrogen atmosphere for 1h. Finally, the supernatant was collected by centrifugation at 3500rpm for 30min to obtain the MXene nanosheet suspension.
[0126] Preparation of positively charged COF nanosphere suspension: 1 mmol / L of 1,3,5-tris(4-aminobenzene)benzene and 1.5 mmol / L of 2,5-dihydroxyterephthalaldehyde were added to 1000 mL of acetonitrile. After ultrasonic dissolution, 0.01 mmol / L of scandium trifluoromethanesulfonate and 0.01 mmol / L of polyethyleneimine were added. The mixture was then allowed to stand at room temperature for 48 h to obtain a uniformly dispersed COF nanosphere suspension.
[0127] (2) Preparation of sandwich-structured COFs / MXene composite nanofiltration membrane;
[0128] (2.1) After preparing the MXene nanosheet suspension into an ethanol solution of 0.06 mg / mL, it was added to a container; then the microfiltration membrane was fixed on the hollowed-out mold, and the mold was then vertically fixed in the center of the container. Two graphite plates were then used as electrophoresis electrodes and fixed parallel to each other (3 cm apart) on both sides of the mold; then a voltage of 20 V was applied for 2 min, and the mold was removed and allowed to air dry naturally until there was no solvent on the membrane surface. The MXene layer deposition was completed, and a microfiltration membrane with an MXene layer was obtained.
[0129] (2.2) After preparing the COFs nanosphere suspension into a 0.1 mg / mL ethanol solution, it was added to a container; then the mold of the microfiltration membrane with the MXene layer was fixed in the center of the container, and two graphite plates were used as electrophoresis electrodes and fixed on both sides of the mold in parallel and at equal distances (3 cm each); then a voltage of 20 V opposite to that in step (2.1) was applied and maintained for 5 min. After that, the mold was removed and allowed to air dry naturally until there was no solvent on the membrane surface. The COFs layer deposition was completed, and a microfiltration membrane with an MXene layer and a COFs layer from the inside to the outside was obtained.
[0130] (2.3) After preparing the MXene nanosheet suspension into an ethanol solution of 0.06 mg / mL, it was added to the container. Then, the mold of the microfiltration membrane with the MXene layer and the COFs layer was fixed in the center of the container. The mold was then vertically fixed in the center of the container. Two graphite plates were used as electrophoresis electrodes and fixed on both sides of the mold in parallel and at equal distances (3 cm each). Then, a voltage of 20 V in the same direction as in step (2.1) was applied and maintained for 2 min. The mold was then removed and vacuum dried at 20 °C. The MXene layer was deposited and a sandwich structure COFs / MXene composite nanofiltration membrane with COFs in the middle and MXene on both sides was obtained.
[0131] Tests have shown that the COFs / MXene composite nanofiltration membrane exhibits excellent dye separation performance, with a permeability as high as 150.2 L / m³. 2 The membrane exhibits a high rejection rate of 98.7% for Congo red (·h·bar). Furthermore, this excellent performance remains stable even within a pH range of 3–11 and during long-term use. Simultaneously, the COFs / MXene composite nanofiltration membrane also demonstrates superior dye / salt separation performance, achieving a separation factor of 101.1 for Congo red / NaCl.
[0132] Example 7
[0133] (1) Preparation of negatively charged MXene nanosheet suspension and positively charged COFs nanosphere suspension;
[0134] Preparation of negatively charged MXene nanosheet suspension: 1 g titanium carbide, 2.5 g lithium fluoride and 20 mL of 3 mol / L hydrochloric acid were mixed and reacted at 35 °C with a stirring rate of 500 rpm for 48 h; after the reaction, the product was washed with deionized water and centrifuged repeatedly at 3500 rpm until the solution was neutral; then the lower precipitate was dispersed in deionized water and sonicated at 0 °C under a nitrogen atmosphere for 1 h; finally, the supernatant was collected by centrifugation at 3500 rpm for 30 min to obtain the MXene nanosheet suspension.
[0135] Preparation of positively charged COF nanosphere suspension: 3 mmol / L benzidine and 2 mmol / L 1,3,5-tricarboxymethyl phloroglucinol were added to a composite solvent consisting of 500 mL dioxane and 500 mL mesitylene. After ultrasonic dissolution, 2 mmol / L scandium trifluoromethanesulfonate and 0.05 mmol / L KH570 were added, and then the mixture was allowed to stand at room temperature for 48 h to obtain a uniformly dispersed COF nanosphere suspension.
[0136] (2) Preparation of sandwich-structured COFs / MXene composite nanofiltration membrane;
[0137] (2.1) After preparing the MXene nanosheet suspension into a methanol solution of 0.1 mg / mL, it was added to a container; then the microfiltration membrane was fixed on the mold with the center hollowed out, and the mold was then vertically fixed in the center of the container. Two graphite plates were then used as electrophoresis electrodes and fixed parallel to each other (4 cm apart) on both sides of the mold; then a voltage of 60 V was applied for 0.5 min, and the mold was removed and allowed to air dry naturally until there was no solvent on the membrane surface. The MXene layer deposition was completed, and a microfiltration membrane with an MXene layer was obtained.
[0138] (2.2) After preparing the COFs nanosphere suspension into a methanol solution of 0.08 mg / mL, it was added to a container; then the mold of the microfiltration membrane with the MXene layer was fixed in the center of the container, and two graphite plates were used as electrophoresis electrodes and fixed on both sides of the mold in parallel and at equal distances (4 cm each); then a voltage of 60 V opposite to that in step (2.1) was applied and maintained for 15 min. After that, the mold was removed and allowed to air dry naturally until there was no solvent on the membrane surface. The COFs layer deposition was completed, and a microfiltration membrane with an MXene layer and a COFs layer from the inside to the outside was obtained.
[0139] (2.3) After preparing the MXene nanosheet suspension into a methanol solution of 0.1 mg / mL, it was added to the container; then the mold of the microfiltration membrane with the MXene layer and the COFs layer was fixed in the center of the container, and then the mold was vertically fixed in the center of the container. Then, two graphite plates were used as electrophoresis electrodes and fixed on both sides of the mold in parallel and equidistant (both 4 cm); then a voltage of 60 V in the same direction as in step (2.1) was applied for 0.5 min, and then the mold was removed and vacuum dried at 60 °C. The MXene layer was deposited and a sandwich structure COFs / MXene composite nanofiltration membrane with COFs in the middle and MXene on both sides was obtained.
[0140] Tests showed that the COFs / MXene composite nanofiltration membrane exhibits excellent dye separation performance, with a permeability as high as 179.4 L / m³. 2 The membrane exhibits a high rejection rate of 97.5% for Congo red (·h·bar). Furthermore, this excellent performance remains stable even within a pH range of 3–11 and during long-term use. Simultaneously, the COFs / MXene composite nanofiltration membrane demonstrates superior dye / salt separation performance, achieving a separation factor of 86.4 for Congo red / NaCl.
[0141] Example 8
[0142] (1) Preparation of negatively charged MXene nanosheet suspension and positively charged COFs nanosphere suspension;
[0143] Preparation of negatively charged MXene nanosheet suspension: 4.8 g titanium carbide, 6.8 g lithium fluoride and 60 mL of 9 mol / L hydrochloric acid were mixed and reacted at 45 °C with a stirring rate of 400 rpm for 24 h. After the reaction, the product was washed with deionized water and centrifuged repeatedly at 3500 rpm until the solution was neutral. Then the lower precipitate was dispersed in deionized water and sonicated at 0 °C under a nitrogen atmosphere for 1 h. Finally, the supernatant was collected by centrifugation at 3500 rpm for 30 min to obtain the MXene nanosheet suspension.
[0144] Preparation of positively charged COF nanosphere suspension: 0.5 mmol / L of 1,3,5-tris(4-aminobenzene)benzene and 0.75 mmol / L of 2,5-dimethoxyterephthalaldehyde were added to a composite solvent consisting of 800 mL of dichloromethane and 200 mL of ethanol. After ultrasonic dissolution, 0.5 mmol / L of glacial acetic acid and 0.01 mmol / L of polyethyleneimine were added, and the mixture was allowed to stand at room temperature for 24 h to obtain a uniformly dispersed COF nanosphere suspension.
[0145] (2) Preparation of sandwich-structured COFs / MXene composite nanofiltration membrane;
[0146] (2.1) After preparing the MXene nanosheet suspension into an ethanol solution of 0.05 mg / mL, it was added to a container; then the microfiltration membrane was fixed on a mold with a hollowed-out center, and the mold was then vertically fixed in the center of the container. Two graphite plates were then used as electrophoresis electrodes and fixed parallel to each other (5 cm apart) on both sides of the mold; then a voltage of 30 V was applied for 1.5 min, and the mold was removed and allowed to air dry until there was no solvent on the membrane surface. The MXene layer deposition was completed, and a microfiltration membrane with an MXene layer was obtained.
[0147] (2.2) After preparing the COFs nanosphere suspension into an ethanol solution of 0.08 mg / mL, it was added to a container; then the mold of the microfiltration membrane with the MXene layer was fixed in the center of the container, and two graphite plates were used as electrophoresis electrodes and fixed on both sides of the mold in parallel and at equal distances (5 cm each); then a voltage of 30 V opposite to that in step (2.1) was applied and maintained for 8 min. After that, the mold was removed and allowed to air dry naturally until there was no solvent on the membrane surface. The COFs layer deposition was completed, and a microfiltration membrane with an MXene layer and a COFs layer from the inside to the outside was obtained.
[0148] (2.3) After preparing the MXene nanosheet suspension into an ethanol solution of 0.05 mg / mL, it was added to the container. Then, the mold of the microfiltration membrane with the MXene layer and the COFs layer was fixed in the center of the container. The mold was then vertically fixed in the center of the container. Two graphite plates were used as electrophoresis electrodes and fixed parallel to each other (5 cm apart) on both sides of the mold. Then, a voltage of 30 V in the same direction as in step (2.1) was applied for 1.5 min. The mold was then removed and vacuum dried at 80 °C. The MXene layer was deposited and a sandwich structure COFs / MXene composite nanofiltration membrane with COFs in the middle and MXene on both sides was obtained.
[0149] Tests showed that the COFs / MXene composite nanofiltration membrane exhibits excellent dye separation performance, with a permeability as high as 137.4 L / m³. 2 The membrane exhibits a high rejection rate of 99.2% for Congo red (·h·bar). Furthermore, this excellent performance remains stable even within a pH range of 3–11 and during long-term use. Simultaneously, the COFs / MXene composite nanofiltration membrane also demonstrates superior dye / salt separation performance, achieving a separation factor of 150.2 for Congo red / NaCl.
[0150] Example 9
[0151] (1) Preparation of negatively charged MXene nanosheet suspension and positively charged COFs nanosphere suspension;
[0152] Preparation of negatively charged MXene nanosheet suspension: 2g titanium carbide, 2g lithium fluoride and 30mL 5mol / L hydrochloric acid were mixed and reacted at 55℃ with a stirring rate of 200rpm for 24h. After the reaction, the product was washed with deionized water and centrifuged repeatedly at 3500rpm until the solution was neutral. Then the lower precipitate was dispersed in deionized water and sonicated at 0℃ under a nitrogen atmosphere for 1h. Finally, the supernatant was collected by centrifugation at 3500rpm for 30min to obtain the MXene nanosheet suspension.
[0153] Preparation of positively charged COF nanosphere suspension: 1 mmol / L of 1,3,5-tris(4-aminobenzene)benzene and 1.5 mmol / L of terephthalaldehyde were added to 1000 mL of acetonitrile. After ultrasonic dissolution, 0.01 mmol / L of scandium trifluoromethanesulfonate and 0.04 mmol / L of polyethyleneimine were added. The mixture was then allowed to stand at room temperature for 72 h to obtain a uniformly dispersed COF nanosphere suspension.
[0154] (2) Preparation of sandwich-structured COFs / MXene composite nanofiltration membrane;
[0155] (2.1) After preparing the MXene nanosheet suspension into an ethanol solution of 0.06 mg / mL, it was added to a container; then the microfiltration membrane was fixed on the hollowed-out mold, and the mold was then vertically fixed in the center of the container. Two graphite plates were then used as electrophoresis electrodes and fixed parallel to each other (2 cm apart) on both sides of the mold; then a voltage of 40 V was applied and held for 1 min. After that, the mold was removed and allowed to air dry naturally until there was no solvent on the membrane surface. The MXene layer deposition was completed, and a microfiltration membrane with an MXene layer was obtained.
[0156] (2.2) After preparing the COFs nanosphere suspension into an ethanol solution of 0.05 mg / mL, it was added to a container; then the mold of the microfiltration membrane with the MXene layer was fixed in the center of the container, and two graphite plates were used as electrophoresis electrodes and fixed on both sides of the mold in parallel and equidistant (both 2 cm); then a voltage of 40 V opposite to that in step (2.1) was applied and maintained for 20 min. After that, the mold was removed and allowed to air dry naturally until there was no solvent on the membrane surface. The COFs layer deposition was completed, and a microfiltration membrane with an MXene layer and a COFs layer from the inside to the outside was obtained.
[0157] (2.3) After preparing the MXene nanosheet suspension into an ethanol solution of 0.06 mg / mL, it was added to the container; then the mold of the microfiltration membrane with the MXene layer and the COFs layer was fixed in the center of the container, and then the mold was vertically fixed in the center of the container. Then, two graphite plates were used as electrophoresis electrodes and fixed on both sides of the mold in parallel and equidistant (both 2 cm); then a voltage of 40 V in the same direction as in step (2.1) was applied and held for 1 min. After that, the mold was removed and vacuum dried at 40 °C. The MXene layer was deposited and a sandwich structure COFs / MXene composite nanofiltration membrane with COFs in the middle and MXene on both sides was obtained.
[0158] Tests have shown that the COFs / MXene composite nanofiltration membrane exhibits excellent dye separation performance, with a permeability as high as 190.8 L / m³. 2 The membrane exhibits a high rejection rate of 98.8% for Congo red (·h·bar). Furthermore, this excellent performance remains stable even within a pH range of 3–11 and during long-term use. Simultaneously, the COFs / MXene composite nanofiltration membrane demonstrates superior dye / salt separation performance, achieving a separation factor of 71.9 for Congo red / NaCl.
[0159] Example 10
[0160] (1) Preparation of negatively charged MXene nanosheet suspension and positively charged COFs nanosphere suspension;
[0161] Preparation of negatively charged MXene nanosheet suspension: 1g titanium carbide, 10g lithium fluoride and 80mL 3mol / L hydrochloric acid were mixed and reacted at 60℃ with a stirring rate of 500rpm for 48h. After the reaction, the product was washed with deionized water and centrifuged repeatedly at 3500rpm until the solution was neutral. Then the lower precipitate was dispersed in deionized water and sonicated at 0℃ under a nitrogen atmosphere for 1h. Finally, the supernatant was collected by centrifugation at 3500rpm for 30min to obtain the MXene nanosheet suspension.
[0162] Preparation of positively charged COF nanosphere suspension: 1.5 mmol / L p-phenylenediamine and 1 mmol / L benzene-1,3,5-tricarboxaldehyde were added to 1000 mL acetonitrile, dissolved by sonication, and then 0.04 mmol / L glacial acetic acid and 0.05 mmol / L polyacrylic acid were added. The mixture was then allowed to stand at room temperature for 48 h to obtain a uniformly dispersed COF nanosphere suspension.
[0163] (2) Preparation of sandwich-structured COFs / MXene composite nanofiltration membrane;
[0164] (2.1) After preparing the MXene nanosheet suspension into an ethanol solution of 0.01 mg / mL, it was added to a container; then the microfiltration membrane was fixed on the hollowed-out mold, and the mold was then vertically fixed in the center of the container. Two graphite plates were then used as electrophoresis electrodes and fixed parallel to each other (4 cm apart) on both sides of the mold; then a voltage of 60 V was applied for 3 min, and the mold was removed and allowed to air dry until there was no solvent on the membrane surface. The MXene layer deposition was completed, and a microfiltration membrane with an MXene layer was obtained.
[0165] (2.2) After preparing the COFs nanosphere suspension into a 0.1 mg / mL ethanol solution, it was added to a container; then the mold of the microfiltration membrane with the MXene layer was fixed in the center of the container, and two graphite plates were used as electrophoresis electrodes and fixed on both sides of the mold in parallel and at equal distances (4 cm each); then a voltage of 60 V opposite to that in step (2.1) was applied and maintained for 5 min. After that, the mold was removed and allowed to air dry naturally until there was no solvent on the membrane surface. The COFs layer deposition was completed, and a microfiltration membrane with an MXene layer and a COFs layer from the inside to the outside was obtained.
[0166] (2.3) After preparing the MXene nanosheet suspension into an ethanol solution of 0.01 mg / mL, it was added to the container. Then, the mold of the microfiltration membrane with the MXene layer and the COFs layer was fixed in the center of the container. The mold was then vertically fixed in the center of the container. Two graphite plates were used as electrophoresis electrodes and fixed on both sides of the mold in parallel and at equal distances (4 cm each). Then, a voltage of 60 V in the same direction as in step (2.1) was applied and maintained for 3 min. The mold was then removed and vacuum dried at 30 °C. The MXene layer was deposited and a sandwich structure COFs / MXene composite nanofiltration membrane with COFs in the middle and MXene on both sides was obtained.
[0167] Tests have shown that the COFs / MXene composite nanofiltration membrane exhibits excellent dye separation performance, with a permeability as high as 168.4 L / m³. 2 The membrane exhibits a high rejection rate of 96.9% for Congo red (·h·bar). Furthermore, this excellent performance remains stable even within a pH range of 3–11 and during long-term use. Simultaneously, the COFs / MXene composite nanofiltration membrane also demonstrates superior dye / salt separation performance, achieving a separation factor of 86.9 for Congo red / NaCl.
[0168] Any aspects not covered in this invention are applicable to existing technologies.
Claims
1. A method for preparing a sandwich-structured COFs / MXene composite nanofiltration membrane, characterized in that, The method includes the following steps: (1) Preparation of negatively charged MXene nanosheet suspension and positively charged COFs nanosphere suspension; (2) Preparation of sandwich-structured COFs / MXene composite nanofiltration membrane; (2.1) The microfiltration membrane is placed in an MXene nanosheet suspension, and two electrophoretic electrodes are placed on both sides of the microfiltration membrane. Then, a voltage is applied to deposit MXene on the outer surface of one side of the microfiltration membrane. Then, the membrane is removed, dried to remove the solvent from the membrane surface, and a microfiltration membrane with an MXene layer is obtained. (2.2) Place the microfiltration membrane with the MXene layer obtained in step (2.1) in a COF nanosphere suspension, and then set two electrophoretic electrodes on both sides of the microfiltration membrane with the MXene layer; then apply a voltage opposite to that in step (2.1) to deposit COFs on the outer surface of the side of the microfiltration membrane with the MXene layer; then remove it, dry it to remove the solvent from the membrane surface, and obtain a microfiltration membrane with the MXene layer and COF layer sequentially from the inside to the outside; (2.3) Place the microfiltration membrane with MXene and COFs layers obtained in step (2.2) in an MXene nanosheet suspension, and then set two electrophoretic electrodes on both sides of the microfiltration membrane with MXene and COFs layers; then apply a voltage in the same direction as in step (2.1) to deposit MXene on the outer surface of the microfiltration membrane with COFs layers on the side with COFs layers; then remove it, dry it to remove the solvent from the membrane surface, and obtain a sandwich structure COFs / MXene composite nanofiltration membrane with COFs in the middle layer and MXene on both sides.
2. The method for preparing the sandwich-structured COFs / MXene composite nanofiltration membrane according to claim 1, characterized in that, In step (1), the preparation of the negatively charged MXene nanosheet suspension is specifically as follows: the negatively charged MXene nanosheet suspension is prepared by selective in-situ etching of MAX phase.
3. The method for preparing the sandwich-structured COFs / MXene composite nanofiltration membrane according to claim 1, characterized in that, In step (1), the preparation of the positively charged COFs nanosphere suspension is specifically as follows: the amino monomer and the aldehyde monomer are dissolved in a composite solvent to form a homogeneous mixed solution; then a catalyst is added, and then the solution is allowed to stand to allow the COFs nanospheres to grow fully, thereby obtaining a uniformly dispersed COFs nanosphere suspension.
4. The method for preparing the sandwich structure COFs / MXene composite nanofiltration membrane according to claim 3, characterized in that, In step (1), the molar ratio of the amino group in the amino monomer to the aldehyde group in the aldehyde monomer is 1:1; the concentrations of both the amino monomer and the aldehyde monomer are 0.1~5 mmol / L; the concentration of the catalyst is 0.01~2 mmol / L; the standing temperature is room temperature; and the standing time is 24~72h.
5. The method for preparing the sandwich-structured COFs / MXene composite nanofiltration membrane according to claim 3, characterized in that, In step (1), the amino monomer is 1,3,5-tris(4-aminobenzene), p-phenylenediamine, or benzidine; The aldehyde monomers are terephthalaldehyde, 2,5-dihydroxyterephthalaldehyde, 2,5-dimethoxyterephthalaldehyde, 1,3,5-tricarboxymethyl phloroglucinol or benzene-1,3,5-tricarboxaldehyde. The composite solvent consists of a main solvent and a co-solvent, with the main solvent accounting for 50-100% of the volume of the composite solvent; the main solvent is water, ethanol, acetonitrile, dichloromethane, dioxane, or mesitylene; the co-solvent is acetonitrile, methyl acetate, ethyl acetate, n-butanol, or ethanol; The catalyst is glacial acetic acid, trifluoroacetic acid, scandium trifluoromethanesulfonate, p-toluenesulfonic acid, or a transition metal nitrate.
6. The method for preparing the sandwich-structured COFs / MXene composite nanofiltration membrane according to claim 3, characterized in that, In step (1), a positively charged modifier is added to the mixed solution and then allowed to stand; the positively charged modifier is polyethyleneimine, KH570 or KH550; the concentration of the positively charged modifier is 0.01~0.05 mmol / L.
7. The method for preparing the sandwich-structured COFs / MXene composite nanofiltration membrane according to claim 1, characterized in that, In step (2.1), the microfiltration base membrane is a polyamide microporous membrane; the microfiltration base membrane is fully unfolded; the microfiltration base membrane is set vertically; The concentration of the MXene nanosheet suspension was 0.01~0.1 mg / mL, and the solvent was methanol or ethanol; The two electrophoresis electrodes and the microfiltration membrane are parallel to each other, and the microfiltration membrane is located on the perpendicular bisector of the two electrophoresis electrodes; the distance between the two electrophoresis electrodes and the microfiltration membrane is 1~5cm. The voltage is 10~60V, and the duration is 0.5~3min.
8. The method for preparing the sandwich structure COFs / MXene composite nanofiltration membrane according to claim 1, characterized in that, In step (2.2), the microfiltration membrane with the MXene layer is fully expanded; the microfiltration membrane with the MXene layer is set vertically. The concentration of the COF nanosphere suspension is 0.01~0.1 mg / mL, and the solvent is methanol or ethanol; The two electrophoresis electrodes and the microfiltration membrane with the MXene layer are parallel to each other, and the microfiltration membrane with the MXene layer is located on the perpendicular bisector of the two electrophoresis electrodes; the distance between the two electrophoresis electrodes and the microfiltration membrane with the MXene layer is 1~5cm. The voltage is 10~60V, and the duration is 1~20min.
9. The method for preparing the sandwich-structured COFs / MXene composite nanofiltration membrane according to claim 1, characterized in that, In step (2.3), the microfiltration membrane with MXene and COFs layers is fully expanded; the microfiltration membrane with MXene and COFs layers is set vertically. The concentration of the MXene nanosheet suspension was 0.01~0.1 mg / mL, and the solvent was methanol or ethanol; The two electrophoresis electrodes and the microfiltration membrane with MXene and COFs layers are parallel to each other, and the microfiltration membrane with MXene and COFs layers is located on the perpendicular line between the two electrophoresis electrodes. The distance between the two electrophoresis electrodes and the microfiltration membrane with MXene and COFs layers is 1~5cm; The voltage is 10~60V, and the duration is 0.5~3min.
Citation Information
Patent Citations
Preparation method of modifying composite nanofiltration membrane by building pure COFs interlayer
CN107789992A
Method for modifying the pore size distribution of a microporous separation medium
US4239714A